Delayed presentation of late-onset glutamic aciduria type II: A disease of infancy presenting in an adult - Arida, Abdul; Hamed, Wala; Khaddam, Omar; Alawadhi, Hussain; Hertecant, Jozef (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Glutamic aciduria Type II is an uncommon inborn error of metabolism. It has a rare late-onset variant that can present in adulthood with recurrent lethargy, vomiting, metabolic acidosis, and myopathy. This is a case of a 27-year-old previously healthy gentleman who presented with complains of daily vomiting and generalized body aches that started 3 days after initiation of strenuous exercise and poor oral intake. Initially found to have high anion gap metabolic acidosis, elevated creatinine kinase levels and hypoglycaemia that improved with intravenous fluids. He later deteriorated and he was transferred to the intensive care unit for intubation and monitoring of his mental status. Labs were evident of hyperammonaemia not responding to lactulose. Further management with continuous venovenous hemodialysis (CVVHD) for ammonia clearance was required. This presentation raised the suspicion for metabolic disease and work up done was suggestive of Type II glutaric aciduria. After a long stay of 28 days in the hospital the patient recovered his mental status and was discharged home on carnitine and riboflavin. The diagnosis was confirmed with further genetic testing. He was later found to have concurrent celiac disease that was confirmed by duodenal biopsy.
Keywords: Glutamic aciduria Type II; inborn errors of metabolism; late-onset variant; metabolic acidosis